Exploration of spatiotemporal heterogeneity and socio‑demographic determinants on COVID‑19 incidence rates in Sarawak, Malaysia - Piau, Phang; Jane, Labadin; Suhaila, Jamaluddin; Saira, Aslam; Helmy, Hazmi (Springer Nature, 2023)
Background In Sarawak, 252 300 coronavirus disease 2019 (COVID-19) cases have been recorded with 1 619 fatalities in 2021, compared to only 1 117 cases in 2020. Since Sarawak is geographically separated from Peninsular Malaysia and half of its population resides in rural districts where medical resources are limited, the analysis of spatiotemporal heterogeneity of disease incidence rates and their relationship with socio-demographic factors are crucial in understanding the spread of the disease in Sarawak.